Thermal performance in a tubular heat exchanger with deltawinglets - Tongyote, Pattarapan; Promvonge, Pongjet; Depaiwa, Nattawoot; Jedsadaratanachai, Withada (My University, 2018)
The paper presents an experimental heat transfer enhancement study in a tubular heat exchanger fitted with delta-winglets. The experimental work was conducted by varying the airflow rate in the test tube having a constant wall heat-flux for turbulent regime, Reynolds number (Re) from 5200 to 23,000. Effects of three pitch ratios (PR=P/D=1.5, 2.0 and 3.0) and two attack angles, α = 45° and 60°, of the winglets at a single blockage ratio (BR=b/D = 0.15) on thermal characteristics are examined. The experimental results show that the winglet-inserted tube yields, respectively, the heat transfer, friction factor and thermal performance in the form of TEF around 1.99-4.08, 4.9-14.3 times higher than the plain tube and 0.85-1.85, depending on the operating condition.